Discerning goodness via nonverbal cues: perspectives from high-context cultures - Hashmi, Madiha; Waheed, Moniza (Immigrant Institutet, 2020)
The current study ventured to explore nonverbal behavioral cues associated with the construct of goodness. In a focus-group setting, perceivers from the high-context cultures of Malaysia and China were asked to define goodness and discuss how they interpreted goodness in others. Across all groups (Malaysian and Chinese) a recurring theme consisting of dynamic cues, static cues and paralinguistic cues was frequently cited, with emphasis across the spectrum. The study findings have implications for the areas of nonverbal communication, social judgments, and person perception.